Apolipoprotein E ε4 Allele was Associated With Nonlesional Mesial Temporal Lobe Epilepsy in Han Chinese Population. Issue 9 (March 2016) - Li, Zhimei; Ding, Chengyun; Gong, Xiping; Wang, Xiaofei; Cui, Tao
Abstract : Abstract: Apolipoprotein E ( APOE ) gene has been implicated as one of the genes susceptible to temporal lobe epilepsy (TLE), but the association is inconsistent. We carried out a study to investigate the association of APOEε4 allele with a subtype of TLE-nonlesional mesial temporal lobe epilepsy (NLMTLE) in Han Chinese people. The study consisted of total 308 NLMTLE patients and 302 controls in Han Chinese. The APOE polymorphisms were genotyped using polymerase chain reaction (PCR) DNA sequencing. We compared the frequency of APOEε4 allele and carrying status between NLMTLE patients and control subjects to test for the association of APOEε4 allele with NLMTLE clinical status. Carrying status of APOEε4 allele was significantly associated with the risk of NLMTLE. No effect of APOEε4 allele was found on the age of onset, duration of epilepsy, or frequency of seizure. Moreover, there was no association between APOEε4 allele and hippocampal sclerosis (HS) or febrile convulsion (FC) history. Our study provided an evidence that APOEε4 allele was a possible risk factor for NLMTLE, and further study with a larger sample is needed to warrant this finding.